2016
DOI: 10.1186/s13049-016-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary responses during the cooling and the extracorporeal life support rewarming phases in a porcine model of accidental deep hypothermic cardiac arrest

Abstract: BackgroundThis study aimed to assess cardiac and pulmonary pathophysiological responses during cooling and extracorporeal life support (ECLS) rewarming in a porcine model of deep hypothermic cardiac arrest (DHCA). In addition, we evaluated whether providing a lower flow rate of ECLS during the rewarming phase might attenuate cardiopulmonary injuries.MethodsTwenty pigs were cannulated for ECLS, cooled until DHCA occurred and subjected to 30 min of cardiac arrest. In order to assess the physiological impact of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Optimal rewarming speed is ill-defined in the literature. A proposed maximum speed of 4 °C/h has been proposed [15] while maintaining a temperature gradient between patient and ECMO of maximum 10 °C [16]. An animal study performed on a pig model compared two ECMO flow regimes (1.5 L/min vs. 3 L/min) and two different temperature goals (5 degrees Celsius above body temperature versus 38 degrees Celsius throughout the resuscitation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal rewarming speed is ill-defined in the literature. A proposed maximum speed of 4 °C/h has been proposed [15] while maintaining a temperature gradient between patient and ECMO of maximum 10 °C [16]. An animal study performed on a pig model compared two ECMO flow regimes (1.5 L/min vs. 3 L/min) and two different temperature goals (5 degrees Celsius above body temperature versus 38 degrees Celsius throughout the resuscitation).…”
Section: Discussionmentioning
confidence: 99%
“…Admission arterial gas analysis showed a severe mixed acidosis associated with hypoxia: pH 6.98, PaCO 2 57, and PaO 2 49. Laboratory testing showed anemia with Hb 9.8 g/dL (13)(14)(15)(16)(17)(18), a thrombocytopenia at 65000/mm 3 (150-440 000), and leucopenia with a total white cell count of 2470/mm 3 (3.5-11). Coagulation disorders were also present.…”
Section: Cases Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant differences in rewarming strategies among reports, while the optimal speed of rewarming and ECLS flow are still to be established. Animal studies on a porcine model of accidental deep hypothermia with cardiac arrest revealed that low ECLS flow does not attenuate post-rewarming pulmonary lesions, but decreases cardiac output (25). On the other hand, also in a porcine model, it has been shown that a high temperature delta between the core temperature and ECLS increases lung injury (26).…”
Section: Technical and Practical Considerationsmentioning
confidence: 99%
“…Hypoxia activates aerobic glycolysis and results in lactate production, muscular pain and decrease sensibility of the skin, all signs clinically observed in patients with ischemic limbs due to arterial thrombosis [ 23 ]. Acute or chronic exposure to cold temperature also elicits vasoconstriction of pulmonary arteries, as shown in humans [ [24] , [25] , [26] ], in various mammals [ [27] , [28] , [29] ], and also in broilers showing signs of pulmonary hypertension (PAH), such as larger diameter of the main pulmonary artery and thicker pulmonary artery wall [ 30 ].…”
Section: How Cold Can Promote Extensive Pneumonia?mentioning
confidence: 99%